Pemberdayaan Karang Taruna untuk Kelola Potensi Pesisir Desa Bulakbaru Kabupaten Jepara - Winastuti Dwi Atmanto; Sri Danarto; Widaryanti Wahyu Winarni (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2015)
Bulakbaru village in JeparaDistrict is a village located in the northeastern coast of Java Sea. This village is prone to abrasion. Each year its land was reduced by between 50 to 100 meters. The existing vegetation in the area is only some mangroves, so that the condition of this coastal area has become more extreme. This condition requires efforts to improve and manage the coastal area potential with a variety of methods. Coastal rehabilitation requires strong human resources, equipped with appropriate science and technology for the coastal community. The research aims to encourage karang tarunato manage coastal potential and transfer simple technology for the rehabilitation of the coastal area so that the community can participate actively in preserving a sustainable environment. This programcomprises methods of public education, consultation, diffusion of science and technology, training and mediation. In the implementation of the program it was evident that the community, particularly members of karangtaruna, actively participated in all activities so that they could learn the science and technology and became more open-minded in managing the potential of their coastal village. Large portion of the the coastal rehabilitation technology can be transfered to the community. The village community was able to realize the importance of mutual cooperation to manage their environment in order that it can be sustainable.